Mixed convection boundary layer flow over a permeable vertical flat plate embedded in an anisotropic porous medium - Bachok @ Lati, Norfifah; Mohd Ishak, Anuar; Pop, Ioan (Hindawi Publishing Corporation, 2010)
An analysis is performed to study the heat transfer characteristics of steady mixed convection flow over a permeable vertical flat plate embedded in an anisotropic fluid-saturated porous medium. The effects of uniform suction and injection on the flow field and heat transfer characteristics are numerically studied by employing an implicit finite difference Keller-box method. It is found that dual solutions exist for both assisting and opposing flows. The results indicate that suction delays the boundary layer separation, while injection accelerates it.